Distributed control algorithm for optimal reactive power control in power grids - Khan, Irfan; Li, Zhicheng; Xu, Yinliang; Gu, Wei (International journal of electrical power & energy systems, 2016)
•Distributed reactive power control to minimize power loss, voltage deviation.•Optimal reactive power control is formulated as non-convex problem.•Difference between neighboring bus voltage angles may be ignored.•Effectiveness of the algorithm is validated with centralized approach.•Algorithm has been tested on large power system. Reactive power generation has been commonly used for power loss minimization and voltage profile improvement in power systems. However, the opportunity cost of reactive power generation should be considered since it affects the frequency control capability of the generator to some degree. This paper proposed a distributed nonlinear control based algorithm to achieve the optimal reactive power generation for multiple generators in a power grid. The reactive power control setting update for each generator only requires local measurement and information exchange with its neighboring buses. It is demonstrated that the proposed algorithm can reduce the non-convex objective function monotonically till convergence and achieve comparable solutions to the centralized technique: particle swarm optimization with faster convergence speed. The proposed algorithm has been tested on the IEEE 9-bus, 39-bus and 162-bus systems to validate its effectiveness and scalability.